Vibration analysis of seedling picking mechanism based on EEMD-MA - Jin, Xin; Li, Shaofan; Li, Mingyong; Zhu, Xiaowu; Zhao, Guoqing; Liu, Mengnan; Xie, Xiaolin (International Journal of Agricultural and Biological Engineering, 2026)
Aiming at the problems such as high substrate damage rate and low seedling picking success rate of the seedling picking mechanism of automatic vegetable transplanters under high-speed operation, this paper proposes an EEMD-MA method combining signal processing and modal analysis. Taking the cam-linked planetary gear system automatic seedling picking mechanism as the research object, this paper conducts research and analysis on its key component—the planet carrier. Sensitive components of vibration signals are extracted, and it is found that resonance is the critical factor deteriorating seedling picking performance. Subsequently, sequential quadratic programming is adopted to carry out optimal design of the component, and vibration tests as well as seedling picking tests are performed on the optimized seedling picking mechanism. The results show that the amplitude at the sensitive component decreased by 61.36%. At seedling picking speeds of 90, 100, 110, and 120 seedlings per minute, the average seedling picking success rate increased by 3.3%, 3.4%, 2.6%, and 1.8% respectively, while the average substrate damage rate decreased by 13.53%, 11.88%, 9.15%, and 8.12% respectively. The tests verify the effectiveness and practicability of the proposed method. Key words: ensemble empirical modal decomposition; planetary carrier; finite element analysis; vibration signal; seedling picking test DOI: 10.25165/j.ijabe.20261904.10489 Citation: Jin X, Li S F, Li M Y, Zhu X W, Zhao G Q, Liu M N, et al. Vibration analysis of seedling picking mechanism based on EEMD-MA. Int J Agric & Biol Eng, 2026; 19(4): 112–122.